2011
DOI: 10.1128/aem.01915-10
|View full text |Cite
|
Sign up to set email alerts
|

LacI(Ts)-Regulated Expression as an In Situ Intracellular Biomolecular Thermometer

Abstract: In response to needs for in situ thermometry, a temperature-sensitive vector was adapted to report changes in the intracellular heat content of Escherichia coli in near-real time. This model system utilized vectors expressing increasing quantities of ␤-galactosidase in response to stepwise temperature increases through a biologically relevant range (22 to 45°C). As judged by calibrated fluorometric and colorimetric reporters, both whole E. coli cells and lysates expressed significant repeatable changes in ␤-ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
(26 reference statements)
2
19
0
Order By: Relevance
“…In contrast, photoacoustic thermometry can provide a precision of about 0.2 °C [15], which is similar to the 0.1 to 0.8 °C precision obtained from fluorescent dyes of various kinds [11,16]. The activity of temperature-sensitive enzymes is another possible probe, and this gives a precision of about 0.7 °C [17]. Unfortunately, the latter two transduction modalities are also sensitive to the pH and ionic strength of the intracellular environment, both of which are variable.…”
Section: Transduction Of Intracellular Temperaturesupporting
confidence: 57%
“…In contrast, photoacoustic thermometry can provide a precision of about 0.2 °C [15], which is similar to the 0.1 to 0.8 °C precision obtained from fluorescent dyes of various kinds [11,16]. The activity of temperature-sensitive enzymes is another possible probe, and this gives a precision of about 0.7 °C [17]. Unfortunately, the latter two transduction modalities are also sensitive to the pH and ionic strength of the intracellular environment, both of which are variable.…”
Section: Transduction Of Intracellular Temperaturesupporting
confidence: 57%
“…McCabe et al 173 reported the first demonstration of a biomolecular intracellular thermometer through temperature-sensitive mutants of lacI controlling LacZ expression which is sensitive to the intracellular heat content of Escherichia coli in near-real time.…”
mentioning
confidence: 99%
“…Two alternative approaches have been reported very recently. The first is based on transfecting E.coli bacteria with a temperature sensitive vector which increases quantities of β-galactosidase in response to a temperature increment 9 . The heating of individual bacteria was monitored via an increase of the lacZ expression.…”
mentioning
confidence: 99%